Psychological Distress, Drug Use, and Internet Use: The Association with Poor Sleep Quality in a Sample of Secondary School Students - Anthony A. Olashore; Oluyemi O. Akanni; Olaniyi O. Ayilara (SAGE Publishing, 2020)
Sleep problems are common among children and adolescents. Sleep quality plays a significant role in their mental health. We aimed to determine the prevalence of poor sleep quality (PSQ) among secondary school students, identify sociodemographic factors associated with PSQ in this group, and examine the independent associations of psychological distress, stimulant use, and internet use with PSQ. Data were collected from 420 secondary school students from four different schools who were selected using a mixture of convenience and random sampling. A set of questionnaires was administered to collect data, and it consisted of 5 sections measuring: the sociodemographic, drug use, psychological distress, internet use, and sleep quality. A total of 378 questionnaires were analyzed. The participants comprised 174 (46.2%) males and 203 (53.8%) females who were between 10 and 21 years. The mean age was 14.78 years. The prevalence of those who had PSQ was 12.2%. A logistic regression model showed that anxiety (AOR = 1.20, 95% CI: 1.10-1.32), depression (AOR = 1.12, 95% CI: 1.00-1.25), and internet use (AOR = 1.02, 95% CI: 1.00-1.03) were significantly associated with PSQ. PSQ commonly exists among students and has a relationship with their psychological state and potentially addictive behavior, such as internet use. We prescribed the optimal treatment of psychological disorders and addictive behavior, of which sleep problems are a typical fallout.